La facezia nel tardo ’400, forma popolareggiante o raffinato genere umanistico? Sondaggi su un capitolo minore della produzione "letteraria" di Leonardo da Vinci - Amendola, Cristiano (Incontri. Rivista europea di studi italiani, 2020)
The facezia in the late 15th century, popular form or refined humanistic genre? A look into a minor section of Leonardo da Vinci’s "literary" productionThis article briefly traces the general lines of a complex cultural process that led the facezia to assume, through its connection with humanistic rhetoric, a leading role in the context of refined discursive, social, and cultural practices of the courtly life of the second half of the 15th century. By interpreting the facezia in the double meaning of a literary genre and a ‘socialized linguistic act’, a little-known aspect of Leonardo da Vinci's cultural production is re-interpreted within this framework: i.e. those works in which the Master played the role of a perfect vir facetus. The articles discusses three ways in which Leonardo seemed to appeal to the theoretical elaborations promoted by the humanists. Firstly, he uses rhetorical-argumentative jokes in his theoretical writings. Secondly, he uses Poggio’s Liber facetiarum, of which he was a passionate reader, as a source from which he drew ‘learned’ words. Lastly, he collects and writes numerous jokes of erudite or courtly character.